Екологічні інвестиції як пріоритетний напрямок розвитку аграрної сфери економіки - Грицаєнко, Галина Іванівна; Грицаенко, Галина Ивановна; Hrytsaienko, Halyna; Грицаєнко, Микола Ігорович; Грицаенко, Николай Игоревич; Hrytsainko, Mykola (My University, 2021)
UK: В статті проаналізовано місце України в міжнародному Індексі процвітання та субіндексі природного середовища, зроблено загальний висновок про незадовільне еколого-економічне становище. Досліджено динаміку розмірів капітальних інвестицій в охорону природного навколишнього середовища в Запорізькій області та в Україні в цілому, розподіл капітальних інвестицій в регіональному розрізі та за видами природоохоронних заходів. Запропоновано активізувати випуск «зелених» облігацій та «зелене» кредитування, в аграрній сфері – впровадження екологічно безпечних технологій, посилення екологічного контроля, стимулювання органічного виробництва. Використання одержаних результатів дозволить визначити напрями інституційних перетворень, які сприятимуть стимулюванню розвитку екологічного інвестування як пріоритетного напрямку розвитку аграрної сфери економіки. EN: The purpose of the article is to study the current state and prospects of environmental investment as a priority area of national economy. The research uses dialectical methods of cognition of processes and phenomena, including the monographic method (analysis of scientific achievements of Ukrainian and foreign scientists on the problems of investment in environmental protection), abstract-logical (theoretical generalizations and formulation of conclusions). The article analyzes the place of Ukraine in the International Prosperity Index and the sub-index of the natural environment, draws a general conclusion about the unsatisfactory ecological and economic situation. The dynamics of the size of capital investments in environmental protection in Zaporizhia region and in Ukraine as a whole is studied. Despite a significant increase in environmental capital investment in the national currency, in dollar terms, their size has changed slightly. In addition, the country has an uneven distribution of capital investment in the regional context (almost half falls on the Kyiv region) and by type of environmental measures. Most of the costs of environmental protection fall on the own funds of enterprises and organizations. Given the insufficient level of financial opportunities, we propose to intensify the issuance of "green" bonds and "green" lending, in the agricultural sector – the introduction of environmentally friendly technologies, strengthening environmental control, stimulating organic production. An element of scientific novelty is the formulated position on the relevance of capital investments in environmental protection, justification of promising ways to finance them. The use of the obtained results will allow to determine the directions of institutional transformations, which will promote the development of ecological investment as a priority direction of the agrarian economy development. RU: Целью статьи является исследование современного состояния и перспектив развития экологических инвестиций как приоритетного направления развития национальной экономики. В статье проанализированы место Украины в международном Индексе процветания и субиндексы природной среды, сделан общий вывод о неудовлетворительном эколого-экономическом положении. Исследована динамика объемов капитальных инвестиций в охрану природной окружающей среды в Запорожской области и в Украине в целом, распределение капитальных инвестиций в региональном разрезе и по видам природоохранных мероприятий. Предложено активизировать выпуск «зеленых» облигаций и «зеленого» кредитования, в аграрной сфере – внедрение экологически безопасных технологий, усиление экологического контроля, стимулирование органического производства. Использование полученных результатов позволит определить направления институциональных преобразований, которые будут способствовать стимулированию развития экологического инвестирования как приоритетного направления развития аграрной сферы экономики.
Ecological investments as a priority direction of agricultural economic development
Экологические инвестиции как приоритетное направление развития аграрной сферы экономики
Keywords: капітальні інвестиції; охорона природного навколишнього середовища; «зелені» облігації; «зелене» кредитування; еколого-економічне становище; аграрна сфера економіки; capital investments; environmental protection; “green” bonds; “green” lending; ecological and economic situation; agrarian economy; капитальные инвестиции; охрана природной окружающей среды; «зеленые» облигации; «зеленое» кредитование; эколого-экономическое положение; аграрная сфера экономики